2001
DOI: 10.1076/clin.15.3.345.10268
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Poor Performance on the Rey–Osterrieth Complex Figure Test among Children With Learning Difficulties: A Dynamic Assessment Approach

Abstract: A dynamic assessment approach was used to examine the source of poor performance on the Rey-Osterrieth Complex Figure Test (ROCF) among 202 school-age children referred for learning difficulties. The ROCF was administered in the standard format and then in a structured format that highlighted the design's organizational framework. Manipulating encoding in this way improved recall to at least age-level for the majority of children. Those children who did not benefit from the structured format had relatively poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 9 publications
2
31
1
1
Order By: Relevance
“…Specifically, while the memory reproductions of children with rightsided injury were as fragmented as their copies, the reproductions of children with left-sided injury were organized around the core central rectangle (Akshoomoff et al, 2002;Akshoomoff & Stiles, 2003). In a study of children referred for learning problems, performance on the ROCF was poor initially but improved for most children when they were instructed to copy the figure using a structural approach (Kirkwood et al, 2001). The authors concluded that poor initial performance on the ROCF task results from a failure to spontaneously apprehend and utilize the organizing framework inherent in the figure, and may reflect metacognitive rather than basic perceptual or spatial processing deficits in children with learning difficulties.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, while the memory reproductions of children with rightsided injury were as fragmented as their copies, the reproductions of children with left-sided injury were organized around the core central rectangle (Akshoomoff et al, 2002;Akshoomoff & Stiles, 2003). In a study of children referred for learning problems, performance on the ROCF was poor initially but improved for most children when they were instructed to copy the figure using a structural approach (Kirkwood et al, 2001). The authors concluded that poor initial performance on the ROCF task results from a failure to spontaneously apprehend and utilize the organizing framework inherent in the figure, and may reflect metacognitive rather than basic perceptual or spatial processing deficits in children with learning difficulties.…”
Section: Introductionmentioning
confidence: 97%
“…Within the extant pediatric literature, the ROCF has been utilized as a measure of visuospatial perception, learning and memory (Baron, 2000) in research with several populations including typically developing youth (Beebe, Ris, Brown, & Dietrich, 2004), epilepsy (Hernandez et al, 2003), phenylketonuria (Antshel & Waisbren, 2003), preterm children (Waber & McCormick, 1995), learning disabilities (Kirkwood et al, 2001) and ADHD (Sami, Carte, Hinshaw, & Zupan, 2003;Seidman et al, 1995). All of these studies found the ROCF to be a sensitive measure to the cognitive difficulties of the identified clinical group.…”
Section: Rey-osterrieth Complex Figurementioning
confidence: 99%
“…The ROCF has also been used in individuals with traumatic brain injury (Ashton, Donders, & Hoffman, 2005) and individuals with aneurysms of the anterior communicating artery (Diamon & DeLucas, 1996). Within the pediatric literature, the ROCF has been used to measure visuospatial perception, learning, and memory (Baron, 2000) in research with several populations including typically developing youth (Beebe, Ris, Brown, & Dietrich, 2004), and preterm children (Waber & McCormick, 1995), as well as children with phenylketonuria (Antshel & Waisbren, 2003), epilepsy (Hernandez et al, 2003), learning disabilities (Kirkwood, Weiler, Berstein, Forbes, & Waber, 2001), and ADHD (Sami, Carte, Hinshaw, & Zupan, 2003;Seidman et al,1995).…”
Section: Introductionmentioning
confidence: 99%